DGGE Identification of Microorganisms Associated with Borrelia burgdorferi Sensu Lato- or Anaplasma phagocytophilum-Infected Ixodes ricinus Ticks from Northwest Norway - Ann-Kristin Tveten; Andreas Riborg; Hanne Tjelle Vadseth (International Journal of Microbiology)
Ticks acquire a wide range of microorganisms as a natural part of their lifecycle. Bacteria, viruses, and protozoa can be transmitted to ticks during feeding and free-living phases. DGGE profiling is a molecular method to describe the microbial population associated with ticks and demonstrate some of the complexity and variety of tick-borne microorganisms. The present study profiled a total of 120 I. ricinus ticks, which were divided into three equally sized groups. We found that B. burgdorferi s.l.-infected ticks presented a pattern consisting of bacterial Pseudomonas spp. (67.5%), Bacillus spp. (50%), and Sphingomonas spp. (77.5%), while A. phagocytophilum-infected ticks were associated with Pseudomonas spp. (82.5%) and Sphingomonas spp. (57.5%). All profiles had one or more Pseudomonas species present, and the intramitochondrial endosymbiont Candidatus Midichloria mitochondrii was present in more than 25% of the samples. Statistical analysis demonstrated that the microbial communities were not significantly different between the groups and that the groups could not be characterised by a specific microbial population.